Efficacy and safety of antibody induction therapy in the current era of kidney transplantation - Opelz, Gerhard; Unterrainer, Christian; Süsal, Caner; Döhler, Bernd (Nephrology, dialysis, transplantation, 2016)
AbstractBackground. Antibody induction with polyclonal rabbit-antithymocyte globulin (rATG) or an interleukin-2 receptor antagonist (IL−2RA) is widely used in